URGENSI PERAN GANDA BIRO HUKUM JAWA TENGAH SEBAGAI FASILITATOR DAN REGULATOR DALAM PEMBERIAN BANTUAN HUKUM - Khan, Ahmad Roy; Widodo, Wahyu; Nugraheni, Nadea Lathifah (Jurnal Ilmiah Dinamika Hukum, 2026)
The provision of legal aid represents the state’s responsibility to ensure access to justice and legal protection, particularly for impoverished and vulnerable groups. Within the framework of regional governance, this responsibility is carried out by local governments through regional apparatuses with authority in legal affairs, including the Legal Bureau of Central Java Province. This article examines the position and authority of the Central Java Provincial Legal Bureau in the administration of legal aid and analyzes the urgency of its dual role as both facilitator and regulator. This study aims to analyze the legal basis of such authority and the implications of the dual role in the implementation of regional legal aid. The research employs a normative juridical method using statutory and conceptual approaches. The findings indicate that the Legal Bureau of Central Java Province possesses administrative authority derived from the delegation of authority by the governor, enabling it to perform both facilitative and regulatory functions in legal aid administration. However, the absence of explicit regulatory boundaries between these roles potentially leads to overlapping authority. Nevertheless, as long as these roles are exercised in accordance with their legal basis and the principles of good governance, the dual role may function as an effective administrative instrument to ensure the effective delivery of legal aid and the protection of citizens’ rights. Keywords : legal aid, authority, dual role.